The SapA Protein Is Involved in Resistance to Antimicrobial Peptide PR-39 and Virulence of Actinobacillus pleuropneumoniae - Xie, Fang; Wang, Yalei; Li, Gang; Liu, Shuanghong; Cui, Ning; Liu, Siguo; Langford, Paul R.; Wang, Chunlai (Frontiers in Microbiology, 2017)
Antimicrobial peptides are essential to the innate immune defense of the mammal against bacterial infection. However, pathogenic bacteria have evolved multiple strategies to resist and evade antimicrobial peptides, which is vital to bacterial survival and colonization in hosts. PR-39 is a linear porcine antimicrobial peptide containing 39 amino acid residues with a high proline content. Resistance to antimicrobial peptide PR-39 has been observed in Actinobacillus pleuropneumoniae. However, little is known about the factors required for this resistance. In the present study, PR-39 exposure increased the expression of the sapA gene in A. pleuropneumoniae. The sapA gene, which encodes the putative peptide transport periplasmic protein, was deleted from this bacterium. The △sapA mutant showed increased sensitivity to PR-39 compared to the wild-type MD12 and complemented P△sapA strains However, the △sapA mutant did not exhibit any alterations in outer membrane integrity. Scanning electron microscopy showed that the △sapA mutant displayed morphological defects, as indicated by a deformed and sunken shape after PR-39 treatment. In addition, disruption of the SapA protein led to reduced colonization and attenuated virulence of A. pleuropneumoniae in the BALB/c mouse model. Collectively, these data suggest that SapA acts as one mechanism for A. pleuropneumoniae to counteract PR-39-mediated killing. To the best of our knowledge, this is the first study to show a mechanism underlying antimicrobial peptide resistance in A. pleuropneumoniae.